Lignans and diterpenes of three Aristolochia species - Lopes, Lucia M.X. [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Elsevier B.V., 1988)
Phytochemical examination of Aristolochia cymbifera, A. esperanzae and A. galeata led to the isolation of furofuran and dibenzylbutyrolactone type lignans, as well as of clerodane and ent-labdane type diterpenes. Structural assignments for two new ent-labdans are presented and discussed. © 1988.
Keywords: A. esperanzae; A. galeata; Aristolochia cymbifera; Aristolochiaceae; Clerodanes; Diterpenes; Labdanes; Lignans